A Finite Element Variational Multiscale Method Based on Two Local Gauss Integrations for Stationary Conduction-Convection Problems. (5th December 2012) - Jiang, Yu; Mei, Liquan; Wei, Huiming; Tian, Weijun; Ge, Jiatai
Abstract : A new finite element variational multiscale (VMS) method based on two local Gauss integrations is proposed and analyzed for the stationary conduction-convection problems. The valuable feature of our method is that the action of stabilization operators can be performed locally at the element level with minimal additional cost. The theory analysis shows that our method is stable and has a good precision. Finally, the numerical test agrees completely with the theoretical expectations and the " exact solution, " which show that our method is highly efficient for the stationary conduction-convection problems.